Mastery - Greene, Robert (New York : Penguin Books, 2013)
Studying the behavior of classical and contemporary masters in their lifetime demonstrates a challenging but clear course for reaching one's potential. The author uses biographical vignettes to illustrate proven methods for achieving mastery.
Discover you calling: the life's task -- Submit to reality: the ideal apprenticeship -- Absorb the master's power: the mentor dynamic -- See people as they are: social intelligence -- Awaken the dimensional mind: the creative active -- Fuse the intuitive with the rational: mastery
Includes bibliographical references and index.
Keywords: Creativity; Successful people; Success; Self-actualization (Psychology); Self-actualization (Psychology); Success; Successful people